THE IMPORTANCE OF PSYCHOLOGICAL KNOWLEDGE IN THE HEALTH OF THE CHILD'S SPIRITUAL WORLD (Spectrum Journal of Innovation, Reforms and Development, 2022)
The Interdependence of Social Psychogenetics and Psychosomatics Because existence is like infinity, and the more you realize it, the more it drags you into its abyss and plunges you into the abyss. ” But the modern world denies this. Being is human. No matter how simple this little definition is, these two phrases can help you understand everything. The concepts of Psychology, Psychosomatics, and Psychogenetics provide insight into the above considerations. These areas of psychology help to understand the mental world of the individual, Psychosomatics and psychogenetics study the problematic processes that occur in the human psyche through the blocks of the mind and subconscious.The purpose of the study; to shed light on the importance of psychological knowledge in the health of the human psyche.